Study design and baseline results of an open-label cluster randomized community-intervention trial to assess the effectiveness of a modified mass deworming program in reducing hookworm infection in a tribal population in southern India - Sarkar,R; Rose,A; Mohan,VR; Ajjampur,SSR; Veluswamy,V; Srinivasan,R; Muliyil,J; Rajshekhar,V; George,K; Balraj,V; Grassly,NC; Anderson,RM; et al. (Contemporary Clinical Trials Communications, 2016)
Introduction: Hookworm infection is a leading cause of iron deficiency anemia and malnutrition inresource-poor settings. Periodic mass deworming with anthelminthic drugs remains the cornerstone ofhookworm control efforts worldwide. Reinfection following treatment occurs, reflecting the humanhost's inability to acquire immunity following exposure to an untreated reservoir of infection. Thiscluster randomized trial will evaluate the effectiveness of a modified, population-based, massdeworming strategy in reducing hookworm infection in an endemic southern Indian population.Methods: Forty five tribal villages were randomized into three groups: one received annual treatment;the second received two rounds of treatment at 1-month intervals; and the third received four rounds oftreatment e two rounds 1 month apart at the beginning, followed by another two after 6 months. Stoolsamples collected through cross-sectional parasitological surveys pre- and post-intervention, and at 3-monthly intervals for a period of 1 year were tested for presence of hookworm ova. Long-term effectivenessof treatment will be assessed through another survey conducted 2 years after the last treatmentcycle.Results: From a population of 11,857 individuals, 8681 (73.2%) were found to be eligible and consented toparticipate, out-migration being the primary reason for non-participation. Baseline stool samples wereobtained from 2082 participants, with 18.5% having hookworm infection, although majority were lowintensity infections (<2000 eggs per gram of feces).Discussion: This study will help identify the optimal mass deworming strategy that can achieve thegreatest impact in the shortest period of time, particularly in settings where long-term program sustainabilityis a challenge